Publication en accès ouvert et coûts d’Article Processing Charges (APC) en Argentine - Fernanda Beigel; Osvaldo Gallardo; Soledad Gomez; Flavia Prado (Revue d'anthropologie des connaissances)
The proliferation of open access journals presents a difficult dilemma for researchers based in Argentina, due to the high costs of APCs (Article Processing Charges) that create a gap between those who can pay to publish and those who cannot. In the first part of this paper, we analyze the burden of APC in different Latin American countries and the lessons of the studies carried out on these expenditures in the case of Argentina. Then we describe the population of researchers who are the object of the survey, the directors of projects with national funding, as well as the method used and its results. We propose a classification of open access publishing practices with APCs into four groups that include researchers from various disciplines. In each group we can observe different tendencies towards open or closed access publication, the origin of the funds used to pay APCs and the disciplines in which this phenomenon has greater or lesser incidence. Finally, we analyzed the qualitative section of the survey, which includes open questions that a good number of researchers answered, offering an overview of their strategies in the face of the problem and the paths that are foreseen to mitigate its harmful effects.